Ablative fractional resurfacing with laser‐facilitated steroid delivery for burn scar management: Does the depth of laser penetration matter?. Issue 2 (30th September 2019) - Issler‐Fisher, Andrea C.; Fisher, Oliver M.; Haertsch, Peter; Li, Zhe; Maitz, Peter K.M.
Abstract : Background and Objective: To investigate whether the depth of ablative fractional CO2 laser (CO2 ‐AFL) penetration of pathological burn scars influences clinical outcomes. Study Design/Materials and Methods: All patients presenting to the Concord Repatriation General Hospital (CRGH) Scar Clinic received ultrasound measurement at the thickest point of their burn scars. Subsequently, the effect of various CO2 ‐AFL settings (energy which correlates to penetration depths) on different outcome parameters was analysed. Patients were divided into five groups depending on minimal scar penetration depth. Results: Seventy‐eight patients (158 scars) had complete data allowing for analysis. Median scar thickness was 3, 400 μm and median laser scar penetration depth was 900 μm. Scar penetration categories were as follows: 0–25% ( n  = 40), 25–50% ( n  = 67), 50–75% ( n  = 31), 75–100% ( n  = 8), >100% ( n  = 3) of scar thickness. The median reduction in maximum scar thickness was 800 μm following one treatment ( P  < 0.001). However, this effect depended on scar penetration depth, whereby scars that were penetrated ≥75% showed no significant improvement in scar thickness and those penetrated >100% indicated a tendency to become worse. Other assessed outcome parameters included: the Vancouver Scar Scale, the Patient and Observer Scar Assessment Scale, a neuropathic pain score (DN4 Pain Questionnaire), and a pruritus score (modified D4 Pruritus Score). All these factors showed significant improvement in the categories up to 75% scar penetration depth. Conclusions: CO2 ‐AFL scar penetration depth significantly influences subjective and objective pathologic burn scar modulation. The penetration depth of 51–75% achieves the greatest reduction in scar thickness. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.